Station Blackout in unit 1 and analysis of the wind field in the region of Angra dos Reis. (April 2015) - Aguiar, A.S.; Lamego Simoes Filho, F.F.; Alvim, A.C.M.; Pimentel, L.C.G.; Moraes, N.O.
Highlights: Severe accident is one that exceeds the design basis (set of information that identifies the specific functions to be performed by an item from a nuclear facility or specific values chosen for controlling parameters as fundamental reference data for the project). A Station Blackout occurs through loss of external energy and internal energy, consecutively. The external loss by event in the transmission lines. The internal loss by problems in diesel generators. With a Station Blackout, the Plant begins to present problems at your core, due to failure in the cooling and in the residual heat removal. Without the removal of heat from the fuel rods, the temperature in the core increases abruptly and thus arises a series of events. Abstract: Since the Fukushima accident a lot wondered on if a nuclear reactor is really safe and, specifically, if the Plants of Angra are trusted to a severe accident as occurred in Japan. The initiator event in Fukushima was a tsunami which in turn affected the external power system and then the internal power system, through failure of the diesel generators. In the case of Angra dos Reis the initiator event would be by sliding slope, the event most likely to occur, which affect the external network, common fault for all three units and later the internal network in this case, the plant most likely fault on your internal network is the unit 1, due the generators GD1 and GD2 have higher probabilities failure of departure and failure to continue to operate 2.86 × 10 −2 and 2.4 × 10 −3, in comparison with the generators GD3 and CD4, respectively 1.74 × 10 −4 and 9.06 × 10 −4 . With relationship to the dispersibilidade of the pollutant in an eventual liberation for atmosphere, it is inferred by the results of the analysis of the winds of the area that the area presents low capacity dispersive.